A Panel Cointegration Analysis of the Impact of Tourism on Economic Growth: Evidence from the Middle East Region. (15th October 2013) - Saleh, Ali Salman; Assaf, A. George; Ihalanayake, Ranjith; Lung, Sidney
Abstract This paper examines the contribution of tourism industry to the GDP of three selected destinations in the Middle East region: Bahrain, Jordan and Saudi Arabia. We introduce a quadratic functional form and apply the advanced panel cointegration dynamic model with robust estimation to test our hypothesis. Our analysis is based on a comprehensive set of panel data of tourism receipts, education investment, foreign direct investment and fixed capital formation over the period of 1981–2008. The results show a long‐run relationship between tourism growth and GDP. We also show that tourism has a stronger impact on the economy than other related sectors. Copyright © 2013 John Wiley & Sons, Ltd.